Husbands' involvement in delivery care utilization in rural Bangladesh: A qualitative study - Story William T; Burgard Sarah A; Lori Jody R; Taleb Fahmida; Ali Nabeel; Hoque DM Emdadul (BMC, 2012)
Abstract Background A primary cause of high maternal mortality in Bangladesh is lack of access to professional delivery care. Examining the role of the family, particularly the husband, during pregnancy and childbirth is important to understanding women's access to and utilization of professional maternal health services that can prevent maternal mortality. This qualitative study examines husbands' involvement during childbirth and professional delivery care utilization in a rural sub-district of Netrokona district, Bangladesh. Methods Using purposive sampling, ten households utilizing a skilled attendant during the birth of the youngest child were selected and matched with ten households utilizing an untrained traditional birth attendant, or dhatri. Households were selected based on a set of inclusion criteria, such as approximate household income, ethnicity, and distance to the nearest hospital. Twenty semi-structured interviews were conducted in Bangla with husbands in these households in June 2010. Interviews were transcribed, translated into English, and analyzed using NVivo 9.0. Results By purposefully selecting households that differed on the type of provider utilized during delivery, common themes--high costs, poor transportation, and long distances to health facilities--were eliminated as sufficient barriers to the utilization of professional delivery care. Divergent themes, namely husbands' social support and perceived social norms, were identified as underlying factors associated with delivery care utilization. We found that husbands whose wives utilized professional delivery care provided emotional, instrumental and informational support to their wives during delivery and believed that medical intervention was necessary. By contrast, husbands whose wives utilized an untrained dhatri at home were uninvolved during delivery and believed childbirth should take place at home according to local traditions. Conclusions This study provides novel evidence about male involvement during childbirth in rural Bangladesh. These findings have important implications for program planners, who should pursue culturally sensitive ways to involve husbands in maternal health interventions and assess the effectiveness of education strategies targeted at husbands.